Traps, bats and calves: Considerations for the hungarian start - Charniga, A. (EWF Scientific Magazine, 2019)
Two major sources of pain, injury or just discomfort for the weightlifter occur at lumbar spine and knee joints. The lumbar problem can be connected with chronic straining with the trunk tilted significantly away from the vertical. In the same vein, knee pain can arise in connection with a large volume of significant straining over knee angles of 90 - 130°. The starting position of the weightlifter for pull phases of the clean and the snatch is crucial to the successful execution of the exercises. A Hungarian start where one begins to lift from relatively small knee angles 50 - 80° with a disposition of the trunk closer to the vertical is the weakest disposition of the weightlifter's links to begin lifting the barbell. Yet this technique has distinct advantages for performance of the lifts as a whole. The classic start from a knee angle of close to 90° and with a barbell separation within the 110 - 130° range involves the minimum moments on legs and trunk. The high start with large knee angle and trunk close to horizontal is strongest position with the least efficient use of the legs and the greatest strain on the lumbar spine. Advantages of the classic and high start are connected only with the effectiveness of the force generated to separate the barbell from the floor. Not taken into account is the efficacy of the entire motion from pull to descent and fixation of the barbell in the squat. An important factor to consider for lifters whom employ the classic and high start and incorporate significant volumes of power snatch, power clean and pulls in training is that these lifters begin the pull and stop at the nearly the same angles of knee and trunk, i.e., chronic stress from repetitive overload at joint angles where there is highest strain. At least some of the aforementioned repetitive overload stress is mitigated when the weightlifter employs the Hungarian start. There is less strain with knees lifting from the fully flexed disposition. Furthermore, there is less strain on the lumbar spine as the trunk is closer to vertical, i.e., the closer a link tovertical the smaller the moment. A possible advantage of a Hungarian start would be the closer proximity of trunk to vertical; facilitating kinesthetic and spatial awareness of balance in fixing the the barbell in the low squat of the snatch and the clean, i.e., the lifting proceeds from squat to squat. The Hungarian start most effectively utilizes the potential of the all but forgotten muscles in the weightlifter's arsenal: the calf musculature.